PENYULUHAN DAN DEMONTRASI KOMPRES DINGIN PADA PENDERITA FRAKTUR TERTUTUP DI POLI ORTHOPEDI RUMAH SAKIT UMUM KOTA LANGSA TAHUN 2022 - Nora Hayani; Zulkarnaini, Zulkarnaini; Azwarni, Azwarni; Maria Irwani; Zakirullah, Zakirullah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
One of the clinical manifestations felt by fracture patients is pain. Pain in fracture sufferers is sharp and stabbing, One way to reduce pain in fracture patients non-pharmacologically is to apply cold compresses to the pain area. Pain can occur in almost every fracture area, if not treated it can have a dangerous effect that will interfere with the healing process and increase morbidity and mortality. The purpose of the service is to increase the insight, knowledge and willingness of the community to apply cold compresses, especially to patients with closed fractures to reduce pain. Participants in this activity were 48 people with closed fractures at the Orthopedic Poly Hospital, Langsa City General Hospital. This community service method first carried out counseling, demonstration of cold compresses using an ice bottle. The results of community service showed that knowledge after being given counseling increased from 54.2% to 72.9% as well as the intensity of pain from moderate pain to mild pain the participants also said it was very comfortable to be given cold compresses. It is hoped that patients with closed fractures can do therapy non-pharmacological cold compresses to reduce pain and reduce the side effects of using drugs.